Design of UI/UX Website Using the Design Thinking Method for Sukabumi Coffee Center - Muhammad Rahmat Faizal; Lattu, Arny; Permana, M. Anton (Fakultas Teknik Universitas Lambung Mangkurat, 2026)
The rapid development of digital technology encourages businesses to provide accessible and informative digital information media. Sukabumi Coffee Center, as a coffee shop business, still faces challenges in delivering information to customers, as existing information distributed through social media is limited and unstructured. This study aims to design the User Interface (UI) and User Experience (UX) of an informative website for Sukabumi Coffee Center using the Design Thinking method. This method consists of five stages: Empathize, Define, Ideate, Prototype, and Test, which emphasize a user-centered approach. The design process was conducted based on observation, interviews, and literature study to identify user needs and problems. The research results include an informative website design that presents coffee product information, facilities, and shop identity in a structured and easily accessible manner. Usability evaluation was carried out using the System Usability Scale (SUS) involving 10 respondents and resulted in an average score of 90.75. This score indicates that the website falls into the acceptable category, achieves a Grade A usability level, and is classified as best imaginable. The findings demonstrate that the application of the Design Thinking method is effective in producing a user-centered UI/UX website design that enhances user experience and information delivery quality.